Implementation of advanced technologies and other means in dangerous freight transportation - Batarlienė, Nijolė (Transport, 2007)
This article examines types of modern technologies application possibilities in dangerous freight transportation. It is noted that the solution to transport technology problems is based on the improvement of technological supply, the rational usage of informational modeling methodology of the whole transportation process. The aspects of mobile solution of public information and transport are named in this paper. The article presents concrete vehicles and freight tracking on their trips analysis, the principles and methods of their operation. Tracking and localization systems are playing a great role in the transportation of dangerous freight. The newly developed remote identification system for transport facilities and freight are presented. First Published Online: 27 Oct 2010